Intracerebroventricular injection of neuropeptide Y suppresses luteinizing hormone pulses in mice - Young, Lauren, author; McCosh, Richard, advisor; Magee, Christianne, committee member; Moreno, Julie, committee member (Colorado State University. Libraries, 2025)
It is well established that KNDy cells, termed for their coexpression of kisspeptin, neurokinin B, and dynorphin, in the arcuate nucleus of the hypothalamus (ARC) regulate gonadotropin-releasing hormone (GnRH) / luteinizing hormone (LH) pulse generation in mice. KNDy cells are a tightly regulated network of neurons receiving input from numerous afferent cell populations and are responsive to changes in physiological perturbations such as energy status or stress. While metabolic stress has been shown to impair reproduction via suppression of LH pulses, the central mechanism by which this happens is not fully understood. Neuropeptide Y (NPY) is a pleiotropic molecule that is produced in neurons throughout the brain and mediates several physiological processes including energy homeostasis and stress responses. Centrally administered NPY elicits variable effects on LH secretion, which depend on several factors including species, gonadal status, and the site of infusion. Therefore, the objective of this experiment was to determine the in vivo action of central NPY administration on LH secretion in mice. Intracerebroventricular injection (ICV) of NPY robustly suppressed LH pulses in ovariectomized (OVX) female and gonadectomized (GDX) male mice. However, the same treatment in gonad-intact males yielded variable responses, and analysis in estradiol replaced OVX female mice revealed an unexpected suppression of LH following brief isoflurane exposure. In assessment of possible sites of neuroendocrine impairment, we found a statistically significant increase in Pdyn (not Kiss1 or Tac2) mRNA abundance in arcuate nucleus micropunches 1 hour, but not 3 hours after ICV injection of NPY, suggesting cellular changes occurred in KNDy cells. In further support of the hypothesis that NPY impairs KNDy cell activity, we found that animals pretreated with NPY or saline had the same response to exogenous kisspeptin, suggesting GnRH neurons and gonadotrope cells remain fully functional. We conclude that NPY is sufficient to suppress LH secretion in OVX female and GDX male mice and that this suppression is likely mediated by the KNDy cells in the ARC.
Keywords: luteinizing hormone; neuropeptide Y; stress; mice; ICV; reproduction